Development and legal regulation of franchising in Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article is written based on the current “Civil Code of the Republic of Kazakhstan” and the law “On the complex entrepreneurial license of Kazakhstan.” The article deals with the concept of franchising, entrepreneur; rights and obligations, responsibilities of the parties, factors that hinder the development of the franchise, as well as address the issues of legal regulation of franchising. Key words: franchising, entrepreneur, competitor, trade mark, trade name.